Render reinforced with textile threads - Pinto, Jorge (2013)
From a sustainable technical building perspective, this research work aims to investigate the potential of using waste products of the textile industry in building applications. In particular, textile threads as an alternative fiber reinforcement solution for cement based coating mortar. Unfortunately, undesirable and unexpected shrinkage cracking coating mortar is still a relevant concern in the building industry. Taking into account that this building pathology has a huge disproportionate depreciative impact on the overall value of a property, it is important to find building solutions that may contribute to mitigate this technical problem. Meanwhile, finding applications for the waste derived from the textile industry may also result in attractive economical and sustainable solutions. Pieces of fabrics or pieces of textile threads are the most common types of waste resulting from this industry. A 70% cotton and 30% acrylic composition thread was the textile waste considered as a reinforcement fiber in this paper. A preliminary characterization of this composite material was experimentally performed. A parametric study including different fiber sizes, fiber contents and ages of the reinforced coating mortar was carried out. The applicability, the durability and the mechanical behaviour of the proposed reinforced mortar were the main material properties studied in this research work. The obtained experimental results indicate that the studied composite material may be interesting from technological, sustainable and economical points of views.